Increasing rates of subalpine tree mortality linked to warmer and drier summers. (12th March 2021) - Andrus, Robert A.; Chai, Rachel K.; Harvey, Brian J.; Rodman, Kyle C.; Veblen, Thomas T.
Abstract: Warming temperatures and rising moisture deficits are expected to increase the rates of background tree mortality–low amounts of tree mortality (~0.5%–2% year −1 ), characterizing the forest demographic processes in the absence of abrupt, coarse‐scale disturbance events (e.g. fire). When compounded over multiple decades and large areas, even minor increases in background tree mortality (e.g. <0.5% year −1 ) can cause changes to forest communities and carbon storage potential that are comparable to or greater than those caused by disturbances. We examine how temporal variability in rates of background tree mortality for four subalpine conifers reflects variability in climate and climate teleconnections using observations of tree mortality from 1982 to 2019 at Niwot Ridge, Colorado, USA. Individually marked trees (initial population 5, 043) in 13 permanent plots—located across a range of site conditions, stand ages and species compositions—were censused for new mortality nine times over 37 years. Background tree mortality was primarily attributed to stress from unfavourable climate and competition (71.2%) and bark beetle activity (23.3%), whereas few trees died from wind (5.3%) and wildlife impacts (0.2%). Mean annualized tree mortality attributed to tree stress and bark beetles more than tripled across all stands between initial censuses (0.26% year −1, 1982–1993/1994) and recent censuses (0.82% year −1, 2008–2019). Higher rates of tree mortality were related to warmer maximum summer temperatures, greater summer moisture deficits, and negative anomalies in ENSO (La Niña), with greater effects of drought in some subpopulations (tree size, age and species). For example, in older stands (>250 years), larger and older trees were more likely to die than smaller and younger trees. Differences in tree mortality rates and sensitivity to climate among subpopulations that varied by stand type may lead to unexpected shifts in stand composition and structure. Synthesis . A strong relationship between higher rates of tree mortality and warmer, drier summer climate conditions implies that climate warming will continue to increase background mortality rates in subalpine forests. Combined with increases in disturbances and declining frequency of moist‐cool years suitable for seedling establishment, increasing rates of tree mortality have the potential to drive declines in subalpine tree populations. Abstract : Rates of background tree mortality increased from 1982–2019 in subalpine forests in Colorado. Higher rates of background tree mortality occurred during summers with warmer and drier climate conditions. Though the sensitivity of tree mortality to climate differed by tree species and tree size classes, climate warming will continue to increase tree mortality throughout subalpine forests. Image: Recently killed subalpine fir tree in an Engelmann spruce‐subalpine fir forest in Colorado.